Proteinase 3 Interferes With C1q-Mediated Clearance of Apoptotic Cells - Tacnet-Delorme, Pascale; Gabillet, Julie; Chatfield, Simon; Thieblemont, Nathalie; Frachet, Philippe; Witko-Sarsat, Véronique (Frontiers in Immunology, 2018)
Proteinase 3 (PR3) is the autoantigen in granulomatosis with polyangiitis (GPA), an autoimmune necrotizing vasculitis associated with anti-neutrophil cytoplasmic antibodies (ANCA). Moreover, PR3 is a pro- serine protease whose membrane expression can potentiate inflammatory diseases such as ANCA-associated vasculitis andor rheumatoid arthritis.  During apoptosis, PR3 is co-externalized with phosphatidylserine (PS) and is known to modulate the the apoptotic cells clearance of apoptotic cells through a calreticulin-dependent mechanism. The complement protein C1q is one actor mediator of efferocytosis, which is the mechanism of the clearance of altered self-cells, and in particularly of apoptotic cells. Since PR3 and C1q are two proteins involved both involved in immune response modulation and in the clearance of apoptotic cells and immune response modulation and that they share certain common ligands (i.e. calreticulin and PS), we examined their possible interaction. We showed demonstrated that C1q binding was increased to apoptotic cells increases on PR3 expressingapoptotic RBL cells that expressed PR3 and we demonstrated the direct interaction between purified C1q and PR3 molecules as shown byby surface plasmon resonance. In order to better understand the functional consequence of this partnership, we tested the C1q-dependent phagocytosis of the RBL cell line expressing PR3 and showed that PR3 impaired C1q –enhancement of apoptotic cell uptake. These findings shed new light on the respective roles of C1q and PR3 in the elimination of apoptotic cells and suggest a novel potential axis to explore in autoimmune diseases characterized by a defect in apoptotic cell clearance and in the resolution of inflammation.